Measuring Redox Status of Melanoma Cells - Liu-Smith, Feng (Methods Mol Biol, 2016)
Redox homeostasis plays multiple roles in essentially all aspects of cellular function, and hence, reliable methods for measuring cellular or tissue redox status are key elements in understanding the redox related signal pathways. However, in the free radical biology field, there are many controversies on the methods to measure reactive oxygen species. In this chapter we describe our experience in measuring superoxide, hydrogen peroxide, and a general redox status using redox-sensitive green fluorescence proteins (roGFPs) in human melanoma cells.